Inconsciente e linguagem: uma leitura de Freud a Lacan - Caselli, Francisco Rafael Barbosa (2014)
This research presents a reading of the concept of the unconscious as proposed by the texts of Freud and Lacan. We seek to investigate how the notion of “unconscious structured like a language” proposed by Jacques Lacan in his return to Freud contributes to a subversion of the concept of the unconscious in the psychoanalytic field. In the meantime, we highlight the points of bonding and rupture between the perspectives of both authors to mark the effects of Lacan’s proposal of a structured unconscious on the matter of ontology. For such, this research introduces the concept of paradigm according to T. Kuhn, indicating the effects of the Linguistic Turn in the paradigm of language to which Lacanian psychoanalysis is linked. Then, it presents the reading strategy used in this investigation in a dialogue with the field of research in psychoanalysis. From this point on, the concept of the unconscious is approached in three stages. The first one addresses Freud’s “Interpretation of Dreams”. The second one presents the contributions of structuralism to the notion of language as a structure. The final stage investigates Lacan’s dialogue with structuralism and points out the results of such dialogue to his concept of structure and his axiom “the unconscious is structured like a language”.